Problem Based Learning Assisted by Wordwall in Improving Students Mathematical Reflective Thinking Skills - Siti Indah Tsuray'ya; Sri Hastuti Noer; Mella Triana (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
Mathematical reflective thinking skills is one of the higher-order thinking skills that is important to develop because it helps students understand problems, determine solution strategies, and evaluate their thinking processes. However, this ability is still not optimal because students are not yet accustomed to reflecting on the problem-solving process. This study aims to analyze the effect of the Problem Based Learning (PBL) assisted by Wordwall on students' mathematical reflective thinking skill in statistics material. This study uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The research population consisted of 265 eighth-grade students of SMP Negeri 9 Bandar Lampung, with the sample selected using a cluster random sampling technique. The research data were obtained through a mathematical reflective thinking skill test and analyzed using the Mann–Whitney U test. The results showed that the mathematical reflective thinking skill of students who received learning using the PBL assisted by Wordwall was higher than that of students who received direct instruction learning. Thus, the PBL assisted by Wordwall has an effect on students' mathematical reflective thinking skills and can therefore be used as an alternative approach in mathematics learning.